Red Blood Cell Distribution Width-to-Platelet Ratio Predicts 30-Day Mortality in Postoperative Acute Pulmonary Embolism: A Retrospective Cohort Study - Yunchao Xing MD; Wenrui Li MD; Xueming Chen MD; Hai Feng MD (Clinical and Applied Thrombosis/Hemostasis)
Objectives To investigate the correlation between red blood cell distribution width-to-platelet ratio (RPR) and 30-day mortality in patients with postoperative acute pulmonary embolism (PAPE). Methods This retrospective cohort study included patients diagnosed with PAPE who were hospitalized in the general surgery ward of our hospital from January 2019 to January 2024. We collected general clinical parameters and laboratory test results at admission and on the day of PAPE diagnosis. Multivariate analysis was performed to identify independent risk factors associated with 30-day mortality. A nomogram was constructed, and its predictive performance was evaluated. Results 132 patients with PAPE were included in this study, comprising 36 males and 96 females. The median age was 67 years, PAPE occurred on average 3.2 days after primary disease surgery, 18 patients experienced 30-day mortality. Concurrently with DVT (OR: 0.15, 95% CI: 0.04-0.64, P  = .011) and RPR ≥ 0.08 on the diagnosis of PAPE (OR: 9.19, 95% CI: 2.91-29.05, P  < .001) were independently associated with 30-day mortality in PAPE patients. The AUC of the multivariate model was 0.77 (95% CI: 0.63-0.91). The Internal validation of nomogram showed the bootstrap-corrected AUC was 0.82 (95%CI 0.76-0.88). Conclusions RPR on the diagnosis of PAPE is independently associated with the prognosis of PAPE patients. The 30-day mortality prediction model constructed based on independent risk factors demonstrated good predictive performance.